Investigation of Angiogenesis and Wound Healing Potential Mechanisms of Zinc Oxide Nanorods - Hassan, Amr; Elebeedy, Dalia; Matar, Emadeldin R.; Fahmy Mohamed Elsayed, Aly; Abd El Maksoud, Ahmed I. (Frontiers in Pharmacology, 2021)
The angiogenesis process is an important issue in tissue engineering. Zinc oxide nanorods are biocompatible metal capable of generating reactive oxygen species (ROS) that respond to induced angiogenesis through various mechanisms, however, released Zn (II) ions suppress the angiogenesis process. In this study, we fabricated green ZnO nanorods using albumin eggshell as a bio-template and investigate its angiogenic potential through CAM assay as well as excision Wound healing assay. This study demonstrated that Angiogenesis and wound healing processes are depending on pro-angiogenic factors as VEGF expression due to the exiting of ZnO nanorods. Angiogenesis induced via zinc oxide nanorods may develop sophisticated materials to apply in the wound healing field.